One-week cocoa flavanol intake increases prefrontal cortex oxygenation at rest and during moderate-intensity exercise in normoxia and hypoxia - Decroix, L.; Tonoli, C.; Lespagnol, E.; Balestra, C.; Descat, A.; Drittij-Reijnders, M. J.; Blackwell, J. R.; Stahl, W.; Jones, A. M.; Weseler, A. R.; Bast, A.; Meeusen, R.; et al. (Journal of Applied Physiology, 2018)
During exercise in hypoxia, O2 delivery to brain and muscle is compromised, and oxidative stress is elicited. Cocoa flavanols (CF) have antioxidant capacities and can increase blood flow by stimulating endothelial function. We aimed to examine the effects of 7-day CF intake on oxidative stress, nitric oxide production, and tissue oxygenation in response to exercise in normobaric hypoxia (14.3% O2). In a randomized, double-blind, cross-over study, 14 well-trained male cyclists completed four trials: exercise in normoxia or hypoxia, after 7-day CF or placebo intake. Flow-mediated dilation (FMD) was measured before intake of the last dose CF or placebo. One hundred minutes later, 20-min steady-state (SS; 45% VO2max) and 20-min time trial (TT) (cycling) were performed. Blood samples were taken. Prefrontal and muscular oxygenation was assessed by near-infrared spectroscopy. At baseline, FMD was increased by CF. Hypoxia increased exercise-induced elevations in lipid peroxidation and antioxidant capacity. CF suppressed exercise-induced lipid peroxidation but did not influence antioxidant capacity. At rest and during SS, prefrontal and muscular oxygenation was decreased by hypoxia. CF elevated prefrontal oxygenation but did not impact muscular oxygenation. During TT, hypoxia accelerated the exercise-induced decrease in prefrontal oxygenation, but not in muscular oxygenation. During TT, CF did not alter prefrontal and muscular oxygenation. CF did not change plasma nitrite, nitrate, and arginine:citrulline. During high-intensity exercise, CF improved neither tissue oxygenation nor performance in well-trained athletes. At rest and during moderate-intensity exercise, CF reduced exercise-induced lipid peroxidation and partially restored the hypoxia-induced decline in prefrontal oxygenation. NEW & NOTEWORTHY For the first time, we showed that CF had beneficial effects on endothelial function at rest, as well as on prefrontal oxygenation at rest and during moderate-intensity exercise, both in normoxia and hypoxia. Moreover, we showed that CF intake inhibited oxidative stress during exhaustive exercise in hypoxia.